Race in the age of Obama - Cunnigen, Donald; Bruce, Marino A. (Marino Anton) (Bingley, U.K. : Emerald, 2010)
This volume provides the first in-depth examination of the impact of the key sociological issues faced by the new Obama Administration and explores conventional topics on race and ethnic relations as well as delves into new areas of intellectual inquiry regarding the changing scope of race relations in a global context. Leading scholars look at: African/American relations through the prism of American and African scholars; the connection between religion, Obama the individual and Obama the President; how the Obama election and presidency have implications for gender identity and sexual politics in the short and long term; the impact the Obama family and their presence in the White House have on existing ideas about the concept of family and related issues; implications for class relations in the United States; specific aspects of the American educational system; social justice issues with an emphasis on understanding their sociological context in relationship to the Obama Administration; and American involvement in the Iraq and Afghanistan War. In addition, the volume examines the 2008 Presidential Election, with emphasis on Obamas road to success.
Introduction / Marino Bruce, Donald Cunnigen -- Obama and Africa / Robert E. Washington -- 'He loves strong, intelligent women. They're his Kryptonite' : Michelle Obama, gender, race and the black press / Michael C. Thornton -- Outsiders within the higher circles : two first ladies as cultural icons in a racialized politics of difference / Cheryl Townsend Gilkes -- Mom-in-chief : community othermothering and Michelle Obama, the First Lady of the people's house / Deborah K. King -- The management of social theory : Obama and the American presidency in the age of segregated diversity / John Sibley Butler -- Struggling to educate its own : the Obama college attainment challenge and the city of Philadelphia / D. Crystal Byndloss -- Racial differences in the perception of racial equality in the Obama era / Melvin E. Thomas, Cedric Herring, Hayward Derrick Horton -- Social justice in the age of Obama / Wornie L. Reed -- Has change really come to America? A black feminist critique of Barack Obama's social justice agenda / Yvonne D. Newsome -- Campaigning for Obama and the politics of race : the case of California, Texas, and beyond / Nadia Y. Kim -- Race threads and race threats : how Obama/race-discourse among conservatives changed through the 2008 presidential campaign / Adam Murphree, Deirdre A. Royster -- The roots of anti-Obama rhetoric / Chip Berlet -- Epilogue / Marino Bruce, Donald Cunnigen.
Keywords: Social Science -- Ethnic Studies -- African American Studies; Social Science -- Ethnic Studies -- General; Social Science -- Discrimination & Race Relations; Ethnic minorities & multicultural studies; Ethnic studies; Race relations; United States -- Race relations